Surface water pollution by some heavy metals in a remote island, Hatiya, northern Bay of Bengal - Mahfuzur Rahman; Ifrat Jahan Chaity; Md. Imam Sohel Hossain; Mohammad Abdul Momin Siddique (Journal of Trace Elements and Minerals, 2024)
Introduction: Metal contamination in surface water in urban cities has become a common scenario in underdeveloped and developing countries. Nowadays, the extent of this contamination is suspected to be traced in remote islands due to the transportation of metals with downward water flow. Unfortunately, we found a dearth of research on our remote island, where thousands of people live and use surface water for their daily needs. Objectives: The current study aims to investigate the status of heavy metals in surface water from a remote island, Hatiya Coast, to determine the existence of heavy metals and their risks to human health. Ten surface water samples were collected, and their concentrations were measured using AAS. Later, various pollution indices were analyzed to understand their pollution level. Results: The mean metal concentrations were ranked in descending order of Mg (65.44 mg.L−1)> Fe (0.375 mg.L−1)> Zn (0.139 mg.L−1)>Mn (0.016 mg.L−1)> and Cu was below the detection limit (BDL). According to different metal pollution indexes, the surface water of the Hatiya coast is low to moderately polluted. The standard HEI value was 1.58, and the range was 1.29–2.25, indicating that all sampling stations had a low level of metal contamination. The mean and range of HPI values were found at 44.58 and 34.33–69.33, respectively. All of the sampling stations indicated low pollution levels except sampling station 6. NPI values revealed moderate contamination in stations 2, 3, and 7. According to the hazard quotient (HQ) and hazard index (HI) for adults and children, heavy metals were found to have no carcinogenic risks for children and adults through dermal exposure. Conclusion: Along with the metals coming from upstream, several local sources of heavy metals were identified during fieldwork, including metallurgical businesses, oil spills from the ship, and some trawlers associated with fishing activities. Overall, these findings would be valuable for aquaculture sectors and future researchers to compare, correlate, and understand the pollution level of the island and serve as a foundation for conducting further investigations in similar island environments, both locally and globally.